(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
This research focuses on the microfacies, sequence stratigraphy and genesis of the upper Devonian phosphate-rich deposits in the Kerman province, SE Iran. These deposits are investigated in the Sarashk and Hutk sections, which are the most complete upper Devonian strata in the studied area. This region was located on the northern coast of the Gondwanaland during the Devonian. Detailed sampling and sedimentological analyses indicate that the studied successions consist of limestone, shale and sandstone lithofacies. The limestone lithofacies includes 12 microfacies and the shale and sandstone lithofacies include two microfacies. Based on the microfacies analysis, five sedimentary sequences are distinguished in each section. The microfacies analyses suggest a mixed carbonate-siliciclastic ramp sedimentary environment. Based on the sequence stratigraphic settings, the phosphorite layers are divided into three types, the first involves lumachella strata and was deposited in transgressive system tract settings; the second was deposited in the high stand system tract and maximum flooding surface settings and the third includes the basal parts of the falling stage system tract setting. The first phosphorite type seems to be a direct result of upwelling currents and blooms in continental shelf deviling creatures, especially brachiopods and fishes. The second, and the most commercially qualified, type formed as an indirect result of upwelling currents and subsequent toxic waters, high mortality and rise of Oxygen Minimum Zone. The third type was a result of post deposition burial digenesis and cementation processes.